2020
DOI: 10.3389/fgene.2020.576235
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compound Heterozygous Variants in MKS1 Leading to Joubert Syndrome

Abstract: Joubert syndrome (JBTS) and Meckel-Gruber syndrome (MKS) are rare recessive disorders caused by defects of cilia, and they share overlapping clinical features and allelic loci. Mutations of MKS1 contribute approximately 7% to all MKS cases and are found in some JBTS patients. Here, we describe a JBTS patient with two novel mutations of MKS1. Whole exome sequencing (WES) revealed c.191-1G > A and c.1058delG compound heterozygous variants. The patient presented with typical cerebellar vermis hypoplasia, hypotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The MKS1 -related genotype–phenotype correlation was proposed as follows: two null alleles of MKS1 result in MKS; one null allele and one non-truncating allele that leaves the B9-C2 domain intact result in JBTS; two non-truncating alleles result in Bardet–Biedl syndrome (BBS, MIM 615990) ( Bader et al, 2016 ; Luo et al, 2020 ). Previous studies have identified the compound heterozygous mutations of MKS1 (p.R158* and p.E471Lfs*92), which disrupted the intracellular localization of MKS1 and induced defects in cilium length and the number of patient fibroblasts ( Slaats et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MKS1 -related genotype–phenotype correlation was proposed as follows: two null alleles of MKS1 result in MKS; one null allele and one non-truncating allele that leaves the B9-C2 domain intact result in JBTS; two non-truncating alleles result in Bardet–Biedl syndrome (BBS, MIM 615990) ( Bader et al, 2016 ; Luo et al, 2020 ). Previous studies have identified the compound heterozygous mutations of MKS1 (p.R158* and p.E471Lfs*92), which disrupted the intracellular localization of MKS1 and induced defects in cilium length and the number of patient fibroblasts ( Slaats et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic MKS1 pathogenic variants have been described in few JBTS patients who usually harbor at least one non-truncating variant [ 5 , 12 , 13 , 14 , 16 , 17 ]. In contrast, biallelic truncating variants in MKS1 are associated with more severe ciliopathies, such as MKS [ 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, biallelic truncating variants in MKS1 are associated with more severe ciliopathies, such as MKS [ 8 , 25 ]. To date, only two reports described biallelic MKS1 truncating variants in individuals presenting a JBTS neurological phenotype with the distinctive ‘molar tooth sign’, hypotonia, developmental delay, intellectual disability, and dysmorphisms [ 16 , 17 ]. One of these patients (homozygous for the c.1461-2A>G splice-site variant, predicted in silico to introduce a PTC) had retinal dystrophy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations